Upaya Guru BK Dalam Meningkatkan Motivasi Belajar Siswa yang Kecanduan Game Online - Safitri, Defa (IJoCE: Indonesian Journal of Counseling and Education, 2023)
The problem in this study is that there are students at SMP Negeri 3 Air Gegas whose learning motivation has decreased due to addiction to online games. So this study aims to describe the condition of the learning motivation of students who are addicted to online games and the efforts of the counseling teacher in increasing the learning motivation of students who are addicted to online games at Air Gegas 3 Public Middle School.This research uses descriptive qualitative research. Sources of data from BK teachers, students, homeroom teachers, and school principals. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis techniques were carried out by data reduction, data presentation, and drawing conclusions. Test the validity of the data using source triangulation and time triangulation. The results of the research show that students who are addicted to online games experience learning motivation and learning grades decrease, a feeling of boredom arises in the subjects in class, and finds it difficult to concentrate on learning. The Counseling Guidance teacher's efforts to increase the learning motivation of students who are addicted to online games for students at Airgegas 3 Public Middle School, namely by implementing services according to student needs, individual services, collaborating between schools, and having extensive knowledge about online games.